Body scores: an overview of choreographic writing (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
From the rudimentary choreographic notations created in the 15th century to the most recent digital methods of motion capture, one observes, on the one hand, the alternation between the presence and absence of the human figure and, on the other, the development of a writing of movement that, starting from the noble intention of preservation and transmission, sometimes ends up being valuable in itself, as a partial result of a creative process. While addressing writing problems specific to music and dance, one perceives in William Forsythe's work a double sense in the use of the score: leading from the work to the notation and from the notation to the work.
Keywords: choreographic notation; motion capture; Body writing; William Forsythe